The Problem of the Historical Fact - Jurkūnaitė, Gema (Problemos, 1979)
It was empirical and metaphysical methodology that gave birth to the cult of historical facts and, later, to its contrast – the idea, that a fact is but a product of historical thinking. From the standpoint of dialectical methodology, there are no facts absolutely opposed to theoretical thinking. A fact becomes a fact when included in a definite theoretical context.